Lymphoblastic Involvement of the Bone Marrow as a Cause of Superscan Appearance in (18)F-Fluorodeoxyglucose Positron Emission Tomography/ Computed Tomography - Koç, Zehra Pınar (Mol Imaging Radionucl Ther, 2020)
The (18)F-fluorodeoxylucose (FDG) positron emission tomography (PET) is the gold standard imaging modality in the staging of lymphoma. The superscan appearance in the FDG PET/computerized tomography (CT) imaging might be because of benign diseases or malignant infiltrations. This case report presents lymphomatous blastic infiltration as a cause of superscan appearance in (18)F-FDG PET/CT.